A facile morphology-controllable synthetic route to monodisperse K3PMo12O40▪nH2O crystals. (December 2022) - Yu, C.-H.; Qiang, Z.-M.; Yu, S.-W.; Li, T.-H.; Li, F.; Huttula, M.; Cao, W.
Abstract: Synthesis is the base of experimental chemistry. Herein, monodisperse K3 PMo12 O40 ▪nH2 O polyoxometalates (POMs) with different morphologies have been reached by tuning synthetic conditions of the K/POM ratio, stirring speed and time, and reaction temperatures. Among these factors, the K/POM ratio is identified most critical in morphological controls of the K3 PMo12 O40 ▪nH2 O particles, altering them from cubes to spheres. Additionally, morphological transformations were identified through a self-assembly and Ostwald ripening process, setting a generic synthetic strategy for the POM systems. Such synthetic strategies have substantial applications in catalytic or surface-demanding fields requiring POM materials with controlled morphology. Graphical abstract: In this work, a monodisperse K3 PMo12 O40 ▪nH2 O system with different surface morphologies have been successfully synthesized by changing the molar ratio of [PMo12 O40 ] 3− /K +, the stirring time and speed, the temperature and time, which are crucial for the anisotropic crystal growth and the formation of the core-shell structured microspheres. Furthermore, the morphological transformations were realized through self-assembly and the Oswald ripening process. Image 1 Highlights: The shape-controlled K3 PMo12 O40 ▪nH2 O was successfully prepared. The K/POM ratio governs particle transition from cubic to spherical shape. Nucleation–formation–growth is the process by which KPMo particles form and grow.